2016
DOI: 10.1017/aer.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of effects of compressibility, geometric and flow parameters on the simulation of a synthetic jet behaviour

Abstract: The present paper focuses on a three-dimensional unsteady turbulent synthetic jet to assess the accuracy of a compressible simulation and some important parameters including the simulations of the actuator, cavity height and Reynolds number. The two-equation SST /k − ω turbulence model is used to predict the flow behaviour. Results show that the compressible simulation case is more accurate than the incompressible one and the dynamic mesh exhibits more reliable results than the mass flow inlet boundary in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…Mallinson et al [15] and Mane et al [16] showed that a larger cavity height yields lower induced velocity while decreasing cavity height would produce the opposite effect. Bazdidi-Therani et al [17] agree with this observation in their computational study of a SJ flow in compressible regime using dynamic mesh for modeling the diaphragm deformation. Utturkar [18] observed that changes in the cavity aspect ratio have limited effect on the jet exit; concluding that details of cavity design and diaphragm placement do not have an important role in jet performance.…”
Section: Introductionsupporting
confidence: 64%
“…Mallinson et al [15] and Mane et al [16] showed that a larger cavity height yields lower induced velocity while decreasing cavity height would produce the opposite effect. Bazdidi-Therani et al [17] agree with this observation in their computational study of a SJ flow in compressible regime using dynamic mesh for modeling the diaphragm deformation. Utturkar [18] observed that changes in the cavity aspect ratio have limited effect on the jet exit; concluding that details of cavity design and diaphragm placement do not have an important role in jet performance.…”
Section: Introductionsupporting
confidence: 64%
“…Bazdidi et al [20] simulated a turbulent synthetic jet by two different technics for simulation of the actuator, namely, the mass flow inlet and the dynamic mesh method. They concluded that the compressible flow model presents more accurate results than the incompressible one.…”
Section: Introductionmentioning
confidence: 99%
“…While in some other researches, even with the same range of train velocity, [15,24,28,35,36] the flow is assumed to be compressible. It is good to note that when high-speed trains move at a velocity of around 300 km/h, the compressible flow was necessarily applied [13,20,29,37]. On the other hand, a computer program named subway environment simulation (SES) was widely used for simulating the air flow inside the tunnels.…”
Section: Introductionmentioning
confidence: 99%